Behavioral adaptations in Ameivula ocellifera (Squamata: Teiidae) in response to thermal environmental changes - Raul Fernandes Dantas Sales; Eliza Maria Xavier Freire (Phyllomedusa: Journal of Herpetology, 2019)
Behavioral adaptations in Ameivula ocellifera (Squamata: Teiidae) in response to thermal environmental changes. Lizards rely on external sources to regulate body temperature, but in many species, it is not known whether lizards are able to change their thermoregulatory behaviors in response to variations in thermal environments. The seasonal thermal ecology of three populations of the Brazilian whiptail lizard, Ameivula ocellifera, in northeastern Brazil (two Caatinga sites and one in the Atlantic Forest) was investigated. The relationships between body temperature and microhabitat temperatures (substrate and air), and between body temperature and thermoregulatory behavior (i.e., time of exposure to sunlight classes and time spent basking) were explored. The average body temperatures of the lizards were 38–39°C; these neither varied seasonally nor among populations. Substrate and air temperatures are lower at the natural Caatinga site, and lizards in there spent less time in the shade and more time exposed to the sun. Microhabitat temperatures vary seasonally in natural Caatinga; they are lower in the rainy season, when lizards spent more time exposed to sun and less time in fltered sun. Lizard body temperatures exceeded microhabitat temperatures in the rainy season in all three populations; however, they did not exceed substrate temperature in the dry season. In each of the populations, lizards with low body temperatures during cloudy conditions spent more time basking. Thus, A. ocellifera adjusts its body temperature behaviorally to compensate for seasonal changes in environmental temperatures, as well as geographic thermal variation throughout its range.